Leaderpreneurship in Higher Education: A Bibliometric Analysis - Santoso, Adhi Setyo; Purwoko, Reza Yuridian (President University, 2024)
This study examines the emerging concept of leaderpreneurship in higher education through a comprehensive bibliometric analysis. By analysing 162 documents from 128 sources published between 2014 and 2024, this research explores the convergence of leadership and entrepreneurship in academic settings. The findings indicate significant growth in leaderpreneurship research, with an annual increase of 4.14%, highlighting distinct patterns in both theoretical development and practical implementation. Key themes identified in the analysis include entrepreneurial leadership development, institutional transformation, and ecosystem building within higher education contexts.